Economic justification of corruption risks in the field of healthcare - Anishchenko, M. A.; Oharenko, V.; Аніщенко, Михайло Анатолійович (My University, 2023)
The purpose of the article is to identify the most common corruption offenses in the healthcare sector and their impact on the country's economy, and also to outline the main directions of the state anti-corruption policy in this area. Methodology. The research is based on the study of international treaties ratified by Ukraine, as well as domestic legal acts regulating the activities of the medical sector in the area of combating and preventing corruption. Results. The article analyzes the main directions of anti-corruption policy in the national healthcare system and determines their impact on the economy of the country. It is noted that corruption in this area is inherent in all socio-economic systems of the world, however, it is most widespread in the process of transformation of the economic and social environment. Corruption can manifest itself in various mechanisms. The author analyzes the monitoring of corruption risks in the field of security by Transparency International, which annually determines the Corruption Perceptions Index (CPI), and the European Commission. It is theoretically proven that a decrease in the score of the Corruption Perceptions Index leads to an outflow of capital from the country (one point corresponds to 0.5% of the country's gross domestic product). Using the examples of the United States of America, the Federal Republic of Germany, and Denmark, the paper examines the most common forms of corruption in the healthcare sector, as well as the positive experiences that should be implemented in order to improve the level of economic development of the country. The main corruption risks in the healthcare sector were analyzed. The role of the NAPC and the NABU in combating and preventing corruption in the healthcare sector is revealed. Practical implications. The article outlines the main steps that need to be taken to introduce changes in the direction of anti-corruption activities in private healthcare institutions. The role of the electronic system of public procurement of goods, works and services "ProZorro" in combating and preventing corruption in the healthcare sector is determined. The analytical data of the Independent Anti-Corruption Commission are studied.
Anishchenko M. A. - https://orcid.org/0000-0001-6342-4829
Keywords: economy; healthcare; corruption risks; anti-corruption; economic instruments